A Case Study on Watson's Personal Care Stores Sdn. Bhd. - Chow, Sook Mung (1999)
Since the economic crisis in July 1997, the performance of the retail industry has been affected by reduced consumer expenditure and higher costs of imports. Watson's Personal Care Stores Sdn Bhd, the retail chain store in Malaysia since 1994 was also affected by this economic turmoil. The problems that Watson's faced were the declining of profits plus some internal problems in each department i.e. the Human Resources, Operations and Buying Department. With all the challenges in the retailing industry, Watson's need to overcome the situation and remain competitive in the market. There are 4 strategies that Watson's can adopt to increase the sales and profits of the company i.e. 1) focus on the 4Ps - Product, Price, Place, Promotion; 2) Implement new policy ; 3 ) Providing outstanding service to the customers and 4) Set up the Marketing Department.